Interspeech 2020 2020
DOI: 10.21437/interspeech.2020-2105
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Robot-Based Auxiliary System for Risk Evaluation of COVID-19 Infection

Abstract: In this paper, we propose a real-time robot-based auxiliary system for risk evaluation of COVID-19 infection. It combines real-time speech recognition, temperature measurement, keyword detection, cough detection and other functions in order to convert live audio into actionable structured data to achieve the COVID-19 infection risk assessment function. In order to better evaluate the COVID-19 infection, we propose an end-to-end method for cough detection and classification for our proposed system. It is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Wei et al [63] propose a diagnostic robot for COVID-19. The robot carries out a consultation with a patient whereby the robot can detect coughing events.…”
Section: Patient Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Wei et al [63] propose a diagnostic robot for COVID-19. The robot carries out a consultation with a patient whereby the robot can detect coughing events.…”
Section: Patient Monitoringmentioning
confidence: 99%
“…Have you been to the public areas of high risk in the last 14 days?" [63]. During the consultation, the robot records the dialogue.…”
Section: Patient Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these benefits, only a few robot arms and teleoperated robots have been tested [26]. Other approaches in COVID-19 robotics response include temperature screening [42], [43] and a cough detection algorithm [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such audio-based strategy has profound implication when examining symptomatic cough sounds associated with COVID-19 whereby cough is a primary symptom, alongside fever and fatigue. Convolution Neural Network (CNN)-based systems were trained to detect cough and screen for COVID-19, and reported accuracy exceeding 90% in [ 14 , 15 , 16 ] and while another study had reported 75% accuracy [ 17 ]. Features were extracted (both handcrafted and transfer learned) from a crowd-sourced database containing breathing and cough sounds [ 18 ] and were used to train a support vector machine and ensemble classifiers to screen COVID-19 individuals from healthy controls.…”
Section: Introductionmentioning
confidence: 99%